Recalques de fundações em estacas - Dias, Cláudio Renato Rodrigues (1977)
This monography presents a state-of-the-art concerning with methods for settlements prediction of pile foundation, and estabilishes a few comparisons with field data. Main methods were grouped into: conventional methods; methods based on theory of elasticity; and empirical procedures based on settlement of pile groups. Stress was given upon second group of methods, the elastic parameters being usually chosen through correlations with field data. Among these the one developed by Aoki and Lopes (1975) received greater emphasis, and a computer program was used.